1990
DOI: 10.1007/bf00198797
|View full text |Cite
|
Sign up to set email alerts
|

Localization of glyoxylate-cycle marker enzymes in peroxisomes of senescent leaves and green cotyledons

Abstract: Crude particulate homogenates from leaves of barley (Hordeum vulgare L.), rice (Oryza sativa L.), leaf-beet (Beta vulgaris var. cicla L.) and pumpkin (Cucurbita pepo L.) cotyledons were separated on sucrose density gradients. The peroxisomal fractions appeared at a buoyant density of 1.25 g·cm(-3) and contained most of the activities of catalase (EC 1.11.1.6), and hydroxypyruvate reductase (EC 1.1.1.81) on the gradients. In peroxisomal fractions from detached leaves and green cotyledons incubated in permanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 16 publications
3
44
0
Order By: Relevance
“…More recently, an increase of some peroxisomal activities was found in senescing leaves (7,16) and carnation petals (10). Because sugar starvation occurs during the senescence of leaf tissues (19), it is possible that the stimulation of glyoxysomal or peroxisomal enzymes in senescing leaves or petals is specifically related to the situation of sugar starvation as it is in root tips.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an increase of some peroxisomal activities was found in senescing leaves (7,16) and carnation petals (10). Because sugar starvation occurs during the senescence of leaf tissues (19), it is possible that the stimulation of glyoxysomal or peroxisomal enzymes in senescing leaves or petals is specifically related to the situation of sugar starvation as it is in root tips.…”
Section: Discussionmentioning
confidence: 99%
“…The source of carbon for sucrose synthesis in this case is unlikely to be photosynthesis, but is rather through the P-oxidation of lipids because glyoxysomal pathways are known to increase during senescence (Gut and Matile, 1988;DeBellis et al, 1990). In this regard, the metabolite repression model has previously been suggested for the senescence-associated expression of malate synthase in cucumber cotyledons (Graham et al, 1992).…”
Section: (C) Rbcs (D) Ef-1a (E) Sag2 (F)sag4mentioning
confidence: 91%
“…The glyoxylate cycle enzymes isocitrate lyase and malate synthase are localized in glyoxysomes and play a role in lipid mobilization, both in postgerminative seedlings and in senescent plant tissues (Beevers, 1979;Huang et al, 1983;Trelease and Doman, 1984;Gut and Matile, 1988;De Bellis et al, 1990;De Bellis and Nishimura, 1991). We have shown that genes encoding the two enzymes are transcriptionally active in pollen (Fig.…”
Section: Genes Encoding Glyoxysomal Enzymes Are Expressed In Pollenmentioning
confidence: 99%
“…In plants with cotyledons that become photosynthetically active, the levels of the glyoxylate cycle enzymes decrease and those of the photorespiratory enzymes increase as glyoxysomes are converted into leaf-type peroxisomes when seedlings undergo the transition from heterotrophic to autotrophic growth (Trelease et al, 1971;Becker et al, 1978;Titus and Becker, 1985;Nishimura et al, 1986;Sautter, 1986). Glyoxylate cycle enzyme levels also increase during the senescence of green cotyledons, leaves, and petals as leaf-type peroxisomes are transformed to glyoxysomes, presumably to function in the breakdown of membrane lipids (Gut and Matile, 1988;De Bellis et al, 1990;Landolt and Matile, 1990;De Bellis and Nishimura, 1991;Pistelli et al, 1991;Graham et al, 1992). Thus, glyoxysomal function is induced at several developmental stages.…”
mentioning
confidence: 99%